Teacher Competences: a core challenge for teacher educators - O'Doherty, Teresa (Department of Education and Science, 2009)
This paper recognises that Irish educationalists need to assert and debate the values, knowledge, skills and attitudes that our teachers should acquire, while recognising the limitations of any rubric to describe the essence of a ‘competent’ teacher’. The process of naming our beliefs and values in education has been initiated with the establishment of the Codes of Professional Conduct for Teachers by the Teaching Council. The collaborative and consultative approach taken by the Council in devising these codes has contributed significantly to the recent debate on the issue of teacher competence and ‘competencies’. Within this context the author suggests that it is important for the Irish education community to reconceptualise the term ‘competencies’ and to develop an alternative lexicon that might capture the nature and quality of teaching in Ireland.
Keywords: competency agenda; teacher competence